2013
DOI: 10.2478/jppr-2013-0051
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitor From the Crude Extract of Plant Seeds Affects the Digestive Proteases in Hyphantria Cunea (Lep.: Arctiidae)

Abstract: Proteases are one of the most important digestive enzymes in the midgut of Hyphantria cunea Drury. Proteases are responsible for protein digestion. In the present study, we evaluated the efficiency of some plant inhibitors on proteases in the gut of the H. cunea. Last instar larvae were collected from mulberry trees. The digestive system of the larvae was used as an enzyme source. The total proteolytic and trypsin activity were assessed by the hemoglobin and BApNA, respectively, as the substrate. The evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Trypsin inhibitor activity was reported in seeds of grass pea (Roy, 1980;Wang et al, 1998). Aghaali et al (2013) indicated that protease inhibitor from the crude extract of grasspea seeds was able to inhibit 35% and 100% of the total proteolytic and tryptic activities in digestive systems of Hyphantria cunea pest, respectively. Wu and Whitaker (1990) purified four trypsin and (2)Katepwa þ CEE*; (3) Katepwa þ CEE þ Pefabloc-SC*; (4)Katepwa þ CEE þ EDTA-Na 2 *; (5) Katepwa þ CEE þ Chymostatin*; (6)Katepwa þ CEEþ3,4-dichloroisocoumarin*; (7) Katepwa þ CEE þ Trypsin inhibitor from soybean*; (8)Katepwa þ CEE þ Trypsin inhibitor from egg-white*; (9)Katepwa þ CEE þ Trypsin-chymotrypsin inhibitor*; (10) Katepwa þ CEEþa 2 -macroglobulin*; (11)Katepwa þ CEE þ TLCK-HCl*.…”
Section: Effects Of Plant Extractsmentioning
confidence: 98%
“…Trypsin inhibitor activity was reported in seeds of grass pea (Roy, 1980;Wang et al, 1998). Aghaali et al (2013) indicated that protease inhibitor from the crude extract of grasspea seeds was able to inhibit 35% and 100% of the total proteolytic and tryptic activities in digestive systems of Hyphantria cunea pest, respectively. Wu and Whitaker (1990) purified four trypsin and (2)Katepwa þ CEE*; (3) Katepwa þ CEE þ Pefabloc-SC*; (4)Katepwa þ CEE þ EDTA-Na 2 *; (5) Katepwa þ CEE þ Chymostatin*; (6)Katepwa þ CEEþ3,4-dichloroisocoumarin*; (7) Katepwa þ CEE þ Trypsin inhibitor from soybean*; (8)Katepwa þ CEE þ Trypsin inhibitor from egg-white*; (9)Katepwa þ CEE þ Trypsin-chymotrypsin inhibitor*; (10) Katepwa þ CEEþa 2 -macroglobulin*; (11)Katepwa þ CEE þ TLCK-HCl*.…”
Section: Effects Of Plant Extractsmentioning
confidence: 98%
“…The use of pesticides, though, has been challenged due to some factors including the rapid development of resistance in exposed pests, resurgence of pest populations, environmental pollutions, and unwanted effects on non-target organisms such as pollinators, natural enemies, and humans (Weisenburger 1993;Biondi et al 2012b;Lu et al 2012;El-Naggar and Zidan 2013). Plant-derived (botanical) insecticides have long been considered as environmentally friendly agents which are alternatives to synthetic chemical pesticides for pest management (Agbenin and Marley 2006;Isman 2006;Aghaali et al 2013). A large number of plant substances have been introduced for use as insect anti-feedants or repellents (Isman 2006;Ramos et al 2006;Bacci et al 2007;Mahdavi-Arab et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inhibitors extracted from Alhagi maurorum Medik., Lathyrus sativus L., Vicia faba L., Prosopis farcta Eig. and Panicum miliaceum L. on the digestive protease of the FWW was evaluated and able to inhibit 34.72% and 100% of the total activity of proteolytic and trypsin, respectively (Aghaali, Ghadamyari, Hosseininaveh, & Riseh, ). The bio insecticide efficacy of secondary metabolites from spinosad and azadyrachtines, a group of limonoids, obtained from the seeds of the neem tree ( Azadirachta indica ) was also performed and spinosad exhibited quick action, comparative to that of other bio‐pesticides (Brudea et al., ).…”
Section: Management Options For the Fall‐webwormmentioning
confidence: 99%